(untitled) (Indian Journal of Animal Production and Management, 2016)
A field survey was conducted during the years 2010-2012 in Jalalpore taluka of Navsari district to identify various constraints perceived by dairy animal owners in dairy husbandry practices and data were collected from randomly selected 150 dairy animal owners through personal interview with the help of pre-tested structured schedule. The study revealed that constraints related to adoption of feeding practices ranked first (58.33%) followed by constraints in adoption of health care practices (52.45%), milking practices (50.99%), housing practices (49.6%) and breeding practices (43.05%). High construction cost (66%), lack of own capital (74.67%), high cost of feed (76%), non-availability of green fodder round the year (62%), lack of awareness about treatment of poor quality straw to improve its nutritive value (74.67%), lack of knowledge about silage preparation (76%), lack of knowledge of balanced ration (46.67%), repeat breeding problems in dairy animals (75.33%), low conception rate through A.I. (58.67%), non-remunerative price for milk (80%), high production cost of milk (68%), lack of knowledge in clean milk production (65.33%), high cost of veterinary medicine (70%), problem of mastitis in dairy animals (77.33%) and inadequate knowledge of diseases and their control (68.67%) were major constraints in adoption of improved dairy husbandry practices.